Reduction of the Carbon Footprint in Agricultural Greenhouses - Vourdoubas, John (International Journal of Sustainable Agricultural Research, 2017)
Climate change in the planet is currently creating many environmental, economic and social problems which are probably going to multiply in the near future. Reduction of greenhouse gases emitted from fossil fuels could result in the mitigation of greenhouse effect and the climate change. Agricultural greenhouses consume large amounts of energy mainly derived from fossil fuels, for the cultivation of various crops. Reduction of their carbon footprint is of primary importance to day. In order to investigate the possibilities of reducing their carbon footprint, the energy consumption during their operation has been estimated and the sustainable energy technologies which could be used for substitution of fossil fuels used have been analyzed. It has been found that a modern greenhouse located in Mediterranean region with a covered area of 1,000 m2 and a total annual energy consumption of 200 KWh/m2 emits 76,900 kg CO2 per year. Total elimination of their CO2 emissions could be achieved with the investment of 44,000 € in renewable energy technologies, including solid biomass for heating and solar-PV for power generation and resulting in lower energy cost during their operation. The payback time of the abovementioned investments has been estimated at 4.84 years.